Rethinking power in organizations, institutions, and markets - Courpasson, David; Golsorkhi, Damon; Sallaz, Jeffrey J., 1974- (Research in the sociology of organizations ;, 2012)
In this volume we strive to go beyond the dual approach of power opposing structural/oversocialized perspectives and situational perspectives, through theoretical and empirical contributions stressing power as a. continuously 'living' phenomenon. In particular, the volume will address issues including integrating the various forms of power in Organization Sociology. How can we reconsider the exercise of power as polymorphic and multidimensional? What ontological and epistemological challenges are raised by an integrated perspective of power? How organizational power shapes intra-organizational practices and inter-organizational relations?.